Design for scalability: A case study of the River City curriculum - Clarke, Jody; Dede, Chris (Journal of Science Education and Technology, 2009)
Publisher: Springer KerkoCite.ItemAlsoKnownAs: 10.1007/s10956-009-9156-4 2339240:QUPKNCUZ 2405685:KM59HIC2

Stakeholder Analysis and Social Network Analysis in Natural Resource Management - Prell, Christina; Hubacek, Klaus; Reed, Mark (Society & Natural Resources, 2009)
The increasing use of stakeholder analysis in natural resource management reflects a growing recognition that stakeholders can and should influence environmental decision making. Stakeholder analysis can be used to avoid inflaming conflicts, ensure that the marginalization of certain groups is not reinforced, and fairly represent diverse interests. We present a case study from the Peak District National Park in the United Kingdom, where we used social network analysis to inform stakeholder analysis. This information helped us identify which individuals and categories of stakeholder played more central roles in the network and which were more peripheral. This information guided our next steps for stakeholder selection. The article ends with a discussion on the strengths and limitations of combining social network analysis with stakeholder analysis.
Publisher: Routledge _eprint: https://doi.org/10.1080/08941920802199202 zotzenLib.CopiedFrom: 2339240:TLSREEVC KerkoCite.ItemAlsoKnownAs: 10.1080/08941920802199202 2339240:TLSREEVC 2405685:W8IEPX5K
Keywords: participatory resource management; social network analysis; stakeholder analysis

Blogging as critical praxis: becoming a critical teacher educator in the age of participatory culture - Pascarella, John (McGill University, 2009)
This self-study of becoming a critical teacher educator extends the research on blogs as a vehicle of critical self-reflection in teaching and teacher education. While the primary focus of this thesis is a self-study of the process of becoming a teacher educator, the author presents findings based on discursive data collected from blogs produced by teacher candidates in two case studies, which inform this process of becoming. The case studies are represented as two “strands”: one carried out in Montréal, Quebec, Canada, at McGill University, and the other carried out near Durban, KwaZulu-Natal, South Africa, at the University of KwaZulu-Natal. Like prior studies involving the use of blogs in teacher preparation, this study examines pre-service teachers’ critical engagement with topics and issues endemic to their current field experiences and future careers in K-12 classrooms. The instructional techniques deployed in the case studies adhered to principles of modeling technology integration in order to transform teaching and learning activities by facilitating a learning environment for pre-service teacher candidates informed by the tenets of critical pedagogy. In this vein, this study examines the implementation of a particular instructional strategy, problem-posing pedagogy, as a practice that integrates the use of blogs to aid the achievement of pre-service teacher candidates’ “critical self-engagement” as well as contribute to the author’s development as a critical teacher educator.
ISBN: 978-0-494-61838-7 Publication Title: ProQuest Dissertations and Theses NR61838 Loc in Archive 305106950 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/305106950?accountid=9851 KerkoCite.ItemAlsoKnownAs: 2405685:3MNATQZE 2534378:IZK6PKSA 2534378:L3NWKKA3
Keywords: 0530:Teacher education; 0710:Educational technology; Blogging; Critical praxis; Culture; Education; Educational technology; Participatory culture; Teacher education; Teacher educator; __:import:01; __:match:final; __:matched; __:study_id:2097704; __finaldtb

Qualitative Research: A Guide to Design and Implementation - Merriam, Sharan B. (John Wiley & Sons, 2009)
Praise for the Third Edition of Qualitative Research: "Sharan B. Merriam synthesizes twenty years of developments in qualitative research with clarity and acumen." ?Michael Quinn Patton, author, Qualitative Research and Evaluation Methods "Here is a qualitative research methods book that reinforces the connection between professional experience and qualitative inquiry." ?Robert Stake, author, The Art of Case Study Research and Multiple Case Study Analysis "In this new edition, Sharan Merriam once again presents the world of qualitative research in language engaging and accessible?for new and experienced readers alike. If you can have only one book about qualitative research, this is it!" ?Patricia M. Reeves, associate professor, School of Social Work, University of Georgia "Mystified by qualitative research? You couldn't ask for a better guide than Sharan Merriam, who introduces you to the fundamental concepts of this research method, explains its complex forms, and then shows you exactly how to do a high-quality qualitative study." ?M. Carolyn Clark, coeditor, The International Journal of Qualitative Studies in Education
KerkoCite.ItemAlsoKnownAs: 2339240:N3J2Y93P 2405685:7G2UTPZC
Keywords: Education / General